Hybrid Solution for Mycotic Pseudoaneurysm of Carotid Bifurcation - Giuseppe Deiana; Antonio Baule; Genadi Genadiev Georgiev; Mario Moro; Francesco Spanu; Flavia Urru; Stefano Camparini (Case Reports in Vascular Medicine)
Mycotic pseudoaneurysms of the extracranial carotid artery are rare and need surgical treatment to prevent rupture or embolization. We treated a case of a carotid bifurcation pseudoaneurysm secondary to infection caused by Staphylococcus epidermidis. We successfully treated it using a catheter balloon to obtain carotid bifurcation’s control and replacing the carotid bifurcation with a vein graft. Management involves aneurysmectomy associated with antibiotic therapy and restoration of arterial continuity.